Legal Instruments for Improving the Role of Civil Society Institutions as Subjects of Cultural Policy in the Field of Historical and Cultural Heritage - Martynenko, Igor (Teisė, 2019)
The purpose of this article is to determine the purpose, principles, and essence of integrating law enforcement and control systems exercising state and public control related to countering crimes and offenses in the fields of historical and cultural heritage, thus developing a single system of subjects of law enforcement activity that can be combined with the function of coordination.